Telemedicine Center of Korean Medicine for treating patients with COVID-19: a retrospective analysis - Dong-su Kim; Hongmin Chu; Baek Ki Min; YoungJoo Moon; Seongjun Park; Kwangho Kim; Shin-Hyeok Park; Young-Don Kim; Mideok Song; Gun-hee Choi; Eunkyoung Lee (Integrative Medicine Research)
Background: Since January 2020, novel coronavirus (SARS-Cov-2) – infected pneumonia (COVID-19) rapidly spread in Korea. This study aimed to introduce the Korean Medicine (KM) telemedicine center for treatment of COVID patients in Korea. Methods: This work was a retrospective review of medical records on patients who received at least one telemedicine session from March 9, 2020 to April 12, 2020 provided by the COVID-19 telemedicine center of Korean Medicine. Data on demographic characteristics, treatment frequency, number of consultation were collected. A descriptive statistical analysis was conducted to report characteristics of patients. Results: A total of 1742 patients underwent consultation through KM telemedicine centers. Despite the rapid increase in the number of patients, the telemedicine center provided treatments to an average of 192 patients per day by about an average of 15 doctors. Furthermore, 4552 herbal medicines were prescribed through telemedicine center, among which 1366 cases (30%) being Qing-Fei-Pai-Du-tang. Telemedicine care also has shown that even with patient's residence transition, medical care can be continued without pause. Conclusion: These results show some advantages of the telemedicine center's implementation in terms of the effective use of medical resources and continuous treatment for patients.